Family violence across the life cycle - Elizabeth Hindmarsh
Aims to address clinical questions that general practitioners (GPs) may have in identifying and responding to patients experiencing family violence. Background Family violence covers a range of abuse including child abuse and neglect, intimate partner violence and elder abuse. Each form of abuse has a significant negative impact on health and wellbeing, and patients present to general practice with varying physical and psychological issues. General practice is unique in that it often works with an entire family, which can be challeng-ing and needs to be actively managed. Objective This article aims to address clinical questions that general practitioners (GPs) may have in identifying and responding to patients experiencing family violence. It takes into account the different types of abuse victims experience and how to respond to perpetrators. The recommendations in this article can also apply to same-sex relationships. Discussion Managing family violence requires a whole-of-practice approach to encourage a safe environment in which families can dis-close abuse and where GPs can respond appropriately. Abuse can be inter-generational and GPs have a role in identification, management and referral.   &nbsp